2019
DOI: 10.1002/jsfa.9598
|View full text |Cite
|
Sign up to set email alerts
|

Production of biomolecules of interest to the anxiolytic herbal medicine industry in yellow passionfruit leaves (Passiflora edulis f. flavicarpa) promoted by mycorrhizal inoculation

Abstract: BACKGROUND Our contemporary way of life has led us to consume high amounts of chemically‐synthesized allopathic medicinal products and anxiolytics to which a viable alternative is the use of Passiflora‐based herbal medicines with composition containing vitexin, a flavonoid with anxiolytic and antidepressant properties. Arbuscular mycorrhizal fungi (AMF) are known for enhancing the production of biomolecules, however, increase production of phytochemistry in Passiflora edulis f. flavicarpa has not been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…The fungus was multiplied in the soil, with millet as host, and kept at 4 °C until the time of application. This isolate was favored due to promoting enhanced growth and accumulation of secondary metabolites in yellow passion fruit plants in a recent study …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fungus was multiplied in the soil, with millet as host, and kept at 4 °C until the time of application. This isolate was favored due to promoting enhanced growth and accumulation of secondary metabolites in yellow passion fruit plants in a recent study …”
Section: Methodsmentioning
confidence: 99%
“…The high‐performance liquid chromatograph was equipped with a photodiode array detector, a binary pump, a degasser, an automatic injector, a C 18 column (250 mm × 4.6 mm i.d., particle size 5 μm), and a C 18 pre‐column (4 mm × 3.9 μm). For analysis of the chromatographic data, the computational program Chromeleon version 6.0 (3000‐RS Dionex, Thermo Fisher Scientific®) was used …”
Section: Inoculation and Experiments Executionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the highest colonization rate by AMF can also influence secondary metabolites biosynthesis (Zitter-Eglseer et al, 2015;Oliveira et al, 2019a) (Figure 1).…”
Section: Amf and Production Of Metabolitesmentioning
confidence: 99%
“…In relation to the benefits proportionated to plants, studies reported that AMF inoculation can increase the growth (Tarraf et al, 2015), offer enhanced nutritional uptake (Domokos et al, 2018), improve stress tolerances (He, Zhang, & Tang,2016;Chang et al, 2018) and regulate the production of primary and secondary compounds from plant metabolism (Parada et al, 2019;Paskovic et al, 2019). In this regard, studies were conducted with plants of medicinal interest, registering the increment of biomolecules production, which confer medicinal properties Oliveira et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%